Coping With the Experiences of Intimate Partner Violence Among South African Women: Systematic Review and Meta-Synthesis - Sere, Yalda; Roman, Nicolette V.; Ruiter, Robert A. C. (Frontiers in Psychiatry, 2021)
Background: Intimate Partner Violence (IPV) continues to be a serious problem worldwide. South Africa has high prevalence rates of women experiencing IPV. While much research reports on the prevalence rates, risk factors and consequences of IPV, fewer studies report on how women deal with the experiences of IPV. Objective: This systematic review of the empirical literature aimed to identify and synthesize the best available evidence on women’s experiences of coping with IPV in South Africa. Methods: A four-level search and retrieval strategy using PRISMA and JBI guidelines was conducted, which included critical appraisal, study selection, data extraction, and data synthesis. Ten studies met the eligibility criteria and were included in the review. They were assessed to meet a set threshold (7/10) based on the JBI Critical Appraisal Checklist for Qualitative Research. All studies were published between 2010 and 2020, conducted in South Africa, and used qualitative methodologies to accomplish the overall aim of investigating IPV experiences of women and their responses to it. Results: The total number of women included in the studies were 159. The data extraction yielded 49 findings of which 47 were aggregated into 14 categories and three themes: 1) Help- and support-seeking coping, 2) Emotional regulation coping, 3) Problem avoidance and distraction coping. Help and support seeking coping refers to women’s responses where they seek instrumental aid, advice, comfort and/or understanding from others. Emotional regulation includes responses of women in which their emotions were expressed or regulated. Problem avoidance and distraction coping represent responses of women in which they take efforts to avoid thinking about the problem situation and rather re-shift their focus. Conclusion: Overall, this review found that a variety of coping responses are used by South African women experiencing IPV. The findings point to the need of understanding IPV and responses to it within a broader social context rather than just at the personal level. Approaching IPV at many levels may lead to a change in societal norms, better access to and delivery of services to IPV survivors, more functional family affairs as well as personal well-being and improved quality of life.